The development of fluorescent protein tracing vectors for multicolor imaging of clinically isolated Staphylococcus aureus - Fuminori Kato; Motoki Nakamura; Motoyuki Sugai (Scientific Reports, 2017)
Abstract Recent advances in fluorescent protein technology provide a wide variety of biological imaging applications; however current tools for bio-imaging in the Gram-positive bacterium Staphylococcus aureus has necessitated further developments for fluorescence intensity and for a multicolor palette of fluorescent proteins. To enhance the expression of multicolor fluorescent proteins in clinical S. aureus strains, we developed new fluorescent protein expression vectors, containing the blaZ/sodp promoter consisting of the β-lactamase gene (blaZ) promoter and the ribosome binding site (RBS) of superoxide dismutase gene (sod). We found S. aureus-adapted GFP (GFPsa) driven by the blaZ/sodp promoter was highly expressed in the S. aureus laboratory strain RN4220, but not in the clinical strains, MW2 and N315, harboring the endogenous blaI gene, a repressor of the blaZ gene promoter. We therefore constructed a constitutively induced blaZ/sodp promoter (blaZ/sodp(Con)) by introducing substitution mutations into the BlaI binding motif, and this modification allowed enhanced expression of the multicolor GFP variants (GFPsa, EGFP, mEmerald, Citrine, Cerulean, and BFP) as well as codon-optimized reef coral fluorescent proteins (mCherry and AmCyan) in the S. aureus clinical strains. These new fluorescent probes provide new tools to enhance expression of multicolor fluorescent proteins and facilitate clear visualization of clinical S. aureus strains.